Learning about learning: literacy demands in ‘Singapore’s global university - ﻿T. Ruanni F. Tupas (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2007)
﻿This paper was borne out of a student‟s remark on the failure of his English classes to make him a good English language learner. From the point-of-view of teacher, course designer and coordinator of these courses, I would like to locate this remark in a range of institutional and ideological contexts which shape the student‟s learning. This attempt at explaining the student‟s „failure‟ is not a simple one: it necessitates an understanding of an academic tertiary institution‟s discursive (re)packaging as a global university which has implications for the privileging of certain institutionalized literacy demands in English as an academic language which, in turn, impact on -and resist -the students‟ „real‟ English language needs outside the classroom. This paper argues that the institutional, ideological and discursive closures to my student‟s English language learning, in the end, are also opportunities for change because the university is,borrowing the words of Soudien (2005) about education in general, “one space in which self-reflection is possible”. The issue here is not to transform the university from the „outside‟, but to (re)negotiate terms and policies from „within‟ in order to locate spaces of intervention and resistance to transform the learning process.